THE INFLUENCE OF POLITICAL INSTITUTIONS ON JOB CREATION LAW IN INDONESIA - Yudisatria, Aria (Scientia Integritas Utama, 2023)
The Job Creation Law (Undang-Undang Cipta Kerja) was introduced and passed in Indonesia as an omnibus law, amending over seventy existing laws to streamline regulations and promote economic growth. However, its drafting and approval process raised significant concerns, particularly regarding the lack of transparency, limited public participation, and its potential adverse impact on labor rights and environmental protection. This paper examines the role of political institutions in shaping the law, utilizing the new institutionalism framework to analyze the influence of formal and informal rules on policymaking. The analysis reveals that the President's strong political influence, combined with a dominant coalition in the House of Representatives (DPR), expedited the legislative process at the expense of democratic norms. Civil society, media, and global actors played crucial roles in contesting the law through protests, social media campaigns, and judicial reviews. The Constitutional Court's ruling, which deemed the law conditionally unconstitutional, further underscores the complex interplay of institutional power in Indonesian lawmaking. Ultimately, this study highlights how institutional dynamics and political power affect policymaking, often sidelining democratic principles in favor of efficiency and economic agendas.